Near-field and far-field EMI shielding response of lightweight and flexible MXene-decorated polyester textiles. (March 2022) - Wang, X.-Y.; Liao, S.-Y.; Wan, Y.-J.; Huang, H.-P.; Li, X.-M.; Hu, Y.-G.; Zhu, P.-L.; Sun, R.; Wong, C.-P.
Abstract: The wide application of miniaturized electronics has given rise to new demands for electromagnetic protection, and electromagnetic interference (EMI) shielding materials have been attracted widespread attention. However, most studies focus on the far-field EMI shieling of material. Herein, a facile dip-coating strategy was developed to achieve MXene/WPU composite coated non-woven fabric (MW@NWF) with both excellent near-field and far-field EMI shielding performance. The MW@NWF shows flexible and strong characteristics, and good waterproof performance. The EMI shielding effectiveness (SE) is up to 55 dB with the MXene content of ∼11 wt%, and the near-field shielding performance is as high as about ∼ - 50 dB in the frequency of 1–9 GHz. Moreover, MW@NWF exhibits long-term structure and performance reliability after 500 cycles of bending-release. This study provides a facile and efficient way to achieve lightweight and flexible shielding materials with high-performance of both near-field and far-field EMI shielding. Graphical abstract: Image 1 Highlights: MW@NWF composites were fabricated by dip-coating MXene/WPU on non-woven fabric. The MW@NWF possesses excellent near-field and far-field EMI shielding performance. The MW@NWF can exhibit long-term structure and performance reliability. The work offers a facile way to prepare flexible and waterproof shielding material.